1981
DOI: 10.3133/ofr8138
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of digital seismograms during the Mammoth Lakes, California, earthquake sequence of May-June 1980

Abstract: This report is the first of two open-file reports describing the collection and preliminary analysis of digital seismograms recorded by the U.S. Geological Survey during the Mammoth Lakes, California, earthquake sequence of May-June, 1980. This first report describes the details of data collection and processing, and contains a summary of data gathered. The second report, by Mueller et al (1980), contains preliminary locations, moments, fault plane solutions, and pictures of locatabl'e events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Of the 1500 events that triggered one or more stations, 250 were recorded on three or more stations, and 150 of all the earthquakes had sufficiently clear P and $ wave arrivals to be locatable (Figure 2). Detailed lists of phase arrival times, preliminary hypocentral parameters, individual residuals, and other information about events recorded on three or more stations are given by Mueller et al [1981]. We relocated the aftershocks using a velocity model more appropriate for the mountain stations (discussed below) and found that the new hypocenters shifted south by 1 km or less and that the depths decreased by 1 km or less than those of Mueller et al [1981].…”
Section: Locationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 1500 events that triggered one or more stations, 250 were recorded on three or more stations, and 150 of all the earthquakes had sufficiently clear P and $ wave arrivals to be locatable (Figure 2). Detailed lists of phase arrival times, preliminary hypocentral parameters, individual residuals, and other information about events recorded on three or more stations are given by Mueller et al [1981]. We relocated the aftershocks using a velocity model more appropriate for the mountain stations (discussed below) and found that the new hypocenters shifted south by 1 km or less and that the depths decreased by 1 km or less than those of Mueller et al [1981].…”
Section: Locationsmentioning
confidence: 99%
“…Detailed lists of phase arrival times, preliminary hypocentral parameters, individual residuals, and other information about events recorded on three or more stations are given by Mueller et al [1981]. We relocated the aftershocks using a velocity model more appropriate for the mountain stations (discussed below) and found that the new hypocenters shifted south by 1 km or less and that the depths decreased by 1 km or less than those of Mueller et al [1981]. Differences between the new locations used in this paper and the locations given by Mueller et al [1981] are generally less than the root-mean-square error for the hypocentral parameters listed by Mueller et al [1981].…”
Section: Locationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seismic swarms following this earthquake migrated northward toward Long Valley caldera and culminated on May 25, 1980, with four earthquakes of M > 6 just south of the caldera [Urhammer and Fergusan, 1980]. The intense shaking associated with these events continued with considerable aftershock activity Spudich et al, 1981] that apparently decreased logarithmically with time. of Savage and Clark [1982] by showing a broad swelling of the resurgent dome [Messing et al, 1982;Riley et al, 1982].…”
Section: Introductionmentioning
confidence: 99%